A Preliminary Research on Financing in Enterprises - Elentably, Felix (International Journal of Accounting and Financial Reporting, 2022)
The capital structure theory is a very important question in economy, the modern capital structure theory by Modigliani and Miller is proposed based on the assumption of perfect capital market. The core problem of capital structure is the company financing options, with the vigorous development of the world capital markets, enterprise's financing way has become increasingly flexible and diversified, the enterprise should choose different financing ways according to their own situation, give full consideration to the development, production scale, repayment ability and financing risks. This paper briefly introduces the types of enterprise financing, analyses the Chinese enterprises' financing condition, puts forward some suggestions on the selection of corporate financing patterns.